Wine Sero-Status of Japanese Encephalitis among Kathmandu and Morang Districts of Nepal - Chapagain, A.; Singh, S.; Thapa, D.B.; Bhattarai, D. (International Journal of Applied Sciences and Biotechnology, 2018)
Japanese Encephalitis (JE) a vector borne zoonoitc disease caused by arbovirus of Flavivirus and transmitted by Culex tritaeniorhynchus additionally pig acts as amplifying host for the virus. A total 115 swine serum samples 100 pig farmers from each district were tested against Japanese encephalitis virus (JEV) infection. The collected samples were analyzed by using “Porcine Encephalitis B Virus Antibody Rapid Test Kit”. Among them 17% samples were positive for JE while 83% samples were negative for JE. Total 18% were positive for JE in Morang district while 115.4% were positive for Kathmandu district. There was no significant difference in prevalence of JE in these two districts (p>0.05). In Kathmandu, the prevalence was 15.4% while in Morang it was slightly higher, 18%. 9.5% younger pigs of 3-9 months of age were positive for JE and 20.6% of age above 9 months were positive of JE but were no significant (p>0.05). Similarly, 17.9% female pigs and 14.6% male pigs were positive for JE however difference was not significantly different. In case of breed, no association of pigs with seropositivity (p>0.05), 7 (13.5%) out of 52 local breed pigs and 12 (19.1%) out of 63 were JE positive. The prevalence rate of JEV was higher in Morang district among study area which might be due to several factors like lack of education in pig farmers, non vaccinated pig population and lack of awareness regarding risk factor of JEV. Int. J. Appl. Sci. Biotechnol. Vol 6(4): 373-378